2010
DOI: 10.1096/fj.10-158188
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal hypoxia independent of undernutrition promotes molecular markers of insulin resistance in adult offspring

Abstract: Molecular mechanisms predisposing people to insulin resistance are starting to emerge. Altered insulin signaling for hepatic gluconeogenesis and muscle glucose uptake is thought to play a central role. Development under suboptimal conditions is also known to increase the risk of insulin resistance in adulthood. However, the partial contributions of reduced oxygen vs. nutrient delivery to the fetus, two common adverse conditions in utero, to developmental programming of insulin resistance remain unknown. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 54 publications
1
58
1
1
Order By: Relevance
“…It has recently been demonstrated that the exposure to hypoxia in utero inhibits the expression of hepatic phospho-Akt-1, Akt-2 and PKCz in adult offspring. 68 It is noteworthy that maternal overfeeding may also program liver metabolism. 69 Mice offspring of dams with high fat intake during pregnancy show insulin resistance, reduced glucose transporter-2 expression and hepatic steatosis.…”
Section: Evidence For Liver Programmingmentioning
confidence: 99%
“…It has recently been demonstrated that the exposure to hypoxia in utero inhibits the expression of hepatic phospho-Akt-1, Akt-2 and PKCz in adult offspring. 68 It is noteworthy that maternal overfeeding may also program liver metabolism. 69 Mice offspring of dams with high fat intake during pregnancy show insulin resistance, reduced glucose transporter-2 expression and hepatic steatosis.…”
Section: Evidence For Liver Programmingmentioning
confidence: 99%
“…20,21 Chronic hypoxia impairs carbohydrate metabolism 11 and insulin signaling 23 in the fetal sheep liver, having a programming effect on insulin resistance in the offspring. 24 We propose that fetal hypoxia is likely to have a significant impact on normal liver function in utero via oxidative stress, contributing to altered fetal growth and metabolism.…”
Section: Introductionmentioning
confidence: 97%
“…The pregnancy complications with abnormal fetal development not only significantly increase maternal and infant mortality and morbidity rates, 3–6 but also have long-term adverse effects on adult health, predisposing to cardiovascular and metabolic diseases. 710 The hallmark of preeclampsia is a shallow trophoblast invasion and insufficient spiral artery remodeling, leading to persistent placental hypoxia and the release of various mediators into the maternal circulation resulting in preeclamptic symptoms. 1 …”
Section: Introductionmentioning
confidence: 99%